Contributing to regional decarbonization: Australia's potential to supply zero-carbon commodities to the Asia-Pacific. (1st June 2022) - Burke, Paul J.; Beck, Fiona J.; Aisbett, Emma; Baldwin, Kenneth G.H.; Stocks, Matthew; Pye, John; Venkataraman, Mahesh; Hunt, Janet; Bai, Xuemei
Abstract: The Asia-Pacific has experienced prodigious growth in energy use and is by far the world's largest greenhouse-gas emitting region. Australia has played a leading role in meeting the region's energy and resource needs, becoming the world's largest exporter of coal, liquefied natural gas, iron ore, and alumina. Our analysis shows that these exports are tied to sizeable consequential emissions at the point of use or processing, accounting for about 8.6% of the total greenhouse gas emissions of the Asia-Pacific. The paper investigates three pathways by which Australia could instead export zero-carbon energy and products: direct exports of renewable electricity via sub-sea cables, exports of zero-carbon fuels such as green hydrogen, and the export of "green" metals processed from Australian ores using renewable energy. Carrying out robust, high-level calculations we find that Australia has the land and renewable energy resources to become a key exporter of these commodities. Realization of this potential relies on ongoing cost reductions, growing demand-side interest linked to meeting ambitious emission reduction targets in the region, and the development of cross-border frameworks for clean energy trade. If it were to achieve this goal, Australia could make a sizeable contribution to regional decarbonization via renewable-energy based exports. Highlights: Consequential emissions from existing key Australian exports are estimated. The potential for replacement zero-carbon exports from Australia is analyzed. Land, water, and energy requirements for new zero-carbon exports are calculated. There is the potential to reduce Asia-Pacific greenhouse gas emissions by about 8.6%. Around 2% of Australia's land mass would be required for solar and wind farms.